Energy-efficient cluster head allocation for wireless sensor networks - Low, Jun Qian (Nanyang Technological University, 2023)
The rapid availability of hardware resources and the maturity of communication technology have led to Wireless Sensor Networks (WSN) becoming an enabling technology for many fields. This advancement is due to WSN'S self-organisation, dynamic topology, and highly dense distribution techniques enable it to contribute to many applications. A WSN comprises thousands of sensor nodes connected through electromagnetic waves for information sharing and cooperative processing, which can monitor environmental variables via sensors in an area. Each sensor node has some primary components, such as a battery, sensor, microprocessor and transmitter module. Clustering protocols are one way to lower energy consumption in a WSN. A clustering protocol works by grouping neighbouring sensor nodes. This project delves into the strategies for reducing energy consumption in a WSN that encompasses a restricted zone. The approaches will be discussed in this report.